Educação física escolar e a promoção da saúde: um ponto de vista - Cláudio Delunardo Severino; Bianca Maria Silva (Universidade Estadual do Oeste do Paraná, 2014)
Obesity is considered to be a major health issue, and the teaching of Physical Education at the schools may contribute to create awareness, among the students, about the relevance of practicing physical activities to promote a healthy lifestyle. The present research has as its main objective to highlight aspects related to the contribution of the teaching of Physical Education as a practice that can be understood as another possibility to prevent teenage and child obesity promoting good health practices. The research allowed to conclude that the role of the Physical Education professor at the school institution goes beyond ministering the classes, touching as well the importance of creating a conscience among the professors and the students that it is necessary to include physical activities on everybody's daily routine.